Implementation of the Think Pair Share Strategy and Drill Method in Mufradāt Learning at MTsN 1 Padang: Implementasi Strategi Think Pair Share dan Metode Drill dalam Pembelajaran Mufradāt di MTsN 1 Padang - Ifkar Rasyid; Muhammad Jafar Shodiq; Hafid Arsyad (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2024)
The acquisition of Arabic vocabulary is crucial for the development of students' language proficiency. Therefore, educators must adopt effective strategies to facilitate vocabulary mastery. This study investigates the implementation of the Think Pair Share method combined with the Drill method in teaching Arabic vocabulary. Using a qualitative approach with a case study method, this research employs in-depth interviews and participatory observations, with data analyzed iteratively and comprehensively. The research subjects consisted of eighth-grade students at MTsN 1 Padang. Findings reveal a four-step process in applying the Think Pair Share model integrated with the Drill method for Arabic vocabulary learning. First, the instructor introduces new vocabulary and explains its meaning and usage in sentence contexts. Next, students engage in a cognitive processing phase to internalize the newly introduced vocabulary. Following this, a collaborative phase ensues where students pair up to exchange and reinforce vocabulary through reciprocal teaching. Finally, the synthesized knowledge is shared with the entire class, where the instructor randomly selects pairs to present their understanding of the vocabulary and its applications. This study emphasizes that combining these pedagogical strategies significantly enhances student engagement, both individually and in peer interactions. Additionally, findings indicate that integrating the Drill method as a complementary element to Think Pair Share substantially strengthens students' retention of the taught vocabulary. Keywords: Arabic Vocabulary, Drill Method, Think Pair Share